Philadelphia Paper - Memoranda showing the percentage of the different Expense Accounts in Mining Hematite Ore at the Manhattan Mine, Sharon Station, New York - J. F. Lewis (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1879)
Believing that one of the essential points in mining, as in all other business, is to know the expense incurred in each particular department, I have carefully kept an account with each department for the past three years; and, as it may be of interest to some of our members, I herewith present it to the Institute, reduced to per centages of the total yearly expense, showing the cost for materials, repairs, expenses, tools, team accounts, powder, oil, and fuel, also for labor under its several heads: 1875—Materials. 1875—Labor, Repairs,...040 Expenses,....016 Team,. .. .. .017 Machinery,. .. .055 Tools,..006 Repairs,. .. .027 Improvements,.....030 Washer,. .. .076 Oil ..008 Pit,.. 178 Powder,..,043 Dirt,.. 130 Fuel,. .325 Superintendence,. ..050 .485 .516 100.1 1876—-Materials. 1876-Labor. Repairs,. . • .. .043 Expenses,......012 Team,.011 Machinery,. .. .090 Tools,..005 Repairs,... 027 Improvements,.....007 Washer,. .. .085 I,. ...,015 Pit,.. 139 Powder,. .. .. .030 Dirt,.. 160 Fuel,...321 Superintendence,. ..078 .444 .559 100.3 1877—Materials. 1877—Labor. Repairs,......102 Expenses,......019 Team,..031 Machinery,. .. .050 Tools,..030 Rrpairs,. .. .046 Improvements,....,031 Washer,. .. .057 I,...009 Pit,.....179 Powder,...035 Dirt,.. 162 Fuel,...200 Superintendence,. ..054 .457 .548 100.5 Average for the three years 1875, '76, and '77. Materials. Labor. Repairs,...062 Expenses,...016 Team,..016 Machinery,. .. .065